Sistem perancangan kewangan islam : SPEKIS - Mohd. Mohyin, Mohd. Johari (2006)
Islamic Financial Planning System (SPEKIS) is an alternative for those who used web-based system. The main objective of the system is to built the activity platform for Islamic Financial Planning base on prosedure which has been decided for used by financial consultant and interested individual. For this moment, many financial consultant activities are only in manual which is not computerized. By using this system all financial consultant can increase their service support through the internet with affordable price. At the same time, this system also helps in handling client database with more effective which can generate full report. The system was developed through development model Unified Modelling Language (UML) and the use of Pretext Hyper Processor (PHP) and MySQL database. Among the softwares used in developing the project are Microsoft Dreamweaver MX and Adobe Photoshop 7.0. Through this system applications, financial consultant activity, especially syariah based could be done efficiently.